BUDDHISM: AN OVERVIEW OF ITS PHILOSOPHY AND DEVELOPMENT IN RUSSIA - Darni Yusna (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
It is a positivist philosophy that assumed a religious character, and it appeared in India after the Hindu Brahmin religion in the fifth century B.C. In the beginning, it was opposed to Hinduism and tended to take care of the human being. It also included a call to mysticism and harshness, and the rejection of luxury, and the call for love, tolerance, and doing good. After the death of its founder, it turned into false beliefs of a pagan nature, and its followers exaggerated its founder until he worshipped him. We conducted a literature study by reviewing various sources and using a descriptive analysis approach and a historical approach in presenting this article. It is considered an ethical system and a philosophical doctrine based on philosophical theories, and its teachings are not revelations but rather opinions and beliefs within a religious framework. Old Buddhism differs from New Buddhism in that the former is ethical, while New Buddhism is Buddha's teachings mixed with philosophical views and mental measurements about the universe and life. Buddhism has spread to all corners of the world, including Russia. Buddhism is considered one of the traditional religions in Russia, which is legally part of Russia's historical heritage. In addition to the historical monastic traditions of Buryatia, Kalmykia, and Tuva, Buddhism is now spreading throughout Russia, with some ethnic Russians converting to it. The main form of Buddhism in Russia is the Gelukpa school of Tibetan Buddhism, with other Tibetan traditions in the minority. Although Tibetan Buddhism is most often associated with Tibet, the religion spread to Mongolia, and via Mongolia, it was brought to Russia.